2015
DOI: 10.1016/j.biortech.2015.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of biomass hydrolysates with nucleophilic amino acids enhances alcoholic fermentation

Abstract: Carbonyl compounds generated in biomass pretreatment hinder the biochemical conversion of biomass hydrolysates to biofuels. A novel approach of detoxifying hydrolysates with amino acids for ethanol production was developed. Among the 20 amino acids assessed for their detoxification efficiency and nucleophilicity, cysteine was the most effective one. It increased both ethanol productivity and final yield of biomass hydrolysates from 0.18 (untreated) to 1.77 g/L/h and from 0.02 to 0.42 g/g, respectively. Detoxif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…Besides, the ratio between holocellulose and lignin is important in some conversion processes. For example, for obtaining ethanol through bio-chemical processing, a biomass with a high content of holocellulose is preferred (Xie et al, 2015) (lignin has very low biodegradability properties). However, pyrolysis of biomass with a high percentage of lignin can produce better bio-char yields (Yang et al, 2006).…”
Section: Determination Of Content In Holocelluloses and Ligninmentioning
confidence: 99%
“…Besides, the ratio between holocellulose and lignin is important in some conversion processes. For example, for obtaining ethanol through bio-chemical processing, a biomass with a high content of holocellulose is preferred (Xie et al, 2015) (lignin has very low biodegradability properties). However, pyrolysis of biomass with a high percentage of lignin can produce better bio-char yields (Yang et al, 2006).…”
Section: Determination Of Content In Holocelluloses and Ligninmentioning
confidence: 99%
“…Klinke et al reported 26 degradation products resulted from alkaline treated wheat straw hydrolysates, including acids, furans and phenols [ 13 ]. Although significant efforts have been made to identify the potential inhibitors on microbial fermentation, no single compound has been determined to be the dominant inhibitor [ 15 ]. Furfural and HMF content has been suggested to be the important indicator of prehydrolysate toxicity, but they are not the major inhibitors [ 4 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reaction products of cysteine and inhibitor showed no negative side effects on the fermentation. Additionally, the amino acid treatment is easy to apply, although the viability of the treatment for industrial processes is still unclear [42].…”
Section: Chemical Degradation Of Inhibitorsmentioning
confidence: 99%